Stereotypes About the Elderly Adult Population in Three Age Groups of Carers of Dependent Elderly People - Pabón Poches, Daysy Katherine (2019)
The presence of stereotypes in carers implies unfavourable effects for dependent elderly people. Objective. This qualitative phenomenological study was therefore intended to describe the stereotypes that exist towards elderly adults in caregivers of three age groups (young, middle and older adults). Method. A semi-structured interview was applied to 20 caregivers of dependent older adults. The report was analyzed via axial coding using biological, chronological, psychological and sociological stereotype categories. Results. Positive and negative stereotypes were identified in the three age groups, although negative stereotypes related to biological aspects such as loss and disease prevail.